Content Analysis Of Textbook Evaluation: Assessing Everyday English For Hospitality Professionals - Abdul Syahid; Devi Hanastasya; Shifa Soraya Lestari; Wilda Cahyani; Ahmad Basahil (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study conducts a comprehensive content analysis of the textbook titled